2022
DOI: 10.14366/usg.21044
|View full text |Cite
|
Sign up to set email alerts
|

Speckle tracking ultrasonography as a new tool to assess diaphragmatic function: a feasibility study

Abstract: Speckle tracking ultrasound as a new tool to assess diaphragmatic function: a feasibility study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Fourth, our initial aim was to explore whether speckle tracking ultrasonography could accurately assess diaphragm function. However, before the research started, Fritsch SJ et al published similar research, demonstrating that speckle tracking ultrasonography depicts alterations in diaphragmatic function after surgery better than 2D ultrasonographic measurements [29]. Therefore, we modified the protocol.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourth, our initial aim was to explore whether speckle tracking ultrasonography could accurately assess diaphragm function. However, before the research started, Fritsch SJ et al published similar research, demonstrating that speckle tracking ultrasonography depicts alterations in diaphragmatic function after surgery better than 2D ultrasonographic measurements [29]. Therefore, we modified the protocol.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 2D measurements can only assess the deformation of the diaphragmatic musculature in the transverse direction; longitudinal measures of the contraction direction cannot be obtained. Several studies have been conducted to explore speckle tracking as a promising approach to evaluating diaphragmatic contractility in healthy subjects [15,18,29,35,36]; however, few studies have reported the use of speckle tracking to assess diaphragmatic contractility among mechanically ventilated patients. Fritsch and colleagues reported the feasibility of diaphragmatic speckle tracking in a cohort of 20 patients after an aortocoronary bypass graft procedure [29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations